Location of the appendix at the third trimester of pregnancy: A new approach to old dilemma - ANIK İLHAN, GÖKÇE (TAYLOR & FRANCIS INC, 2015)
The aim of this study was to determine the location of the appendix at the third trimester of pregnancy as there are conflicting results in literature. Distances from the base of the appendix were measured intra-operatively to the anterior iliac spine (A), symphysis pubis (B) and the xyphoid process (C). The same measurements were taken from McBurney's point on the abdominal wall (A1, B1 and C1). In the allocated 21 pregnant and 18 non-pregnant women, distance A and B were 10.3 +/- 0.9 cm and 18.3 +/- 3.2 cm in pregnant and 6.7 +/- 0.9 cm and 13.2 +/- 0.9 cm in non-pregnant women (p < 0.001), respectively. Distance C was shorter in pregnant women (14.7 +/- 2.5 cm vs. 23.8 +/- 1.9, p < 0.001). Conversely, distance C1 was longer in pregnant women (30.3 +/- 3.0 vs. 24.8 +/- 5.1 cm, p = 0.004). This study provides evidence that the appendix moves cranially late in the course of the pregnancy. Therefore, McBurney's point cannot be used as a reference point to localise the appendix at the third trimester of pregnancy.
Keywords: Appendix; appendicitis; pregnancy; ABDOMINAL-PAIN; ACUTE ABDOMEN; MANAGEMENT; OUTCOMES